(untitled) (Semiárida, 2023)
A. In the Magellan Steppe of south Patagonia, degradation of Festuca grasslands leads to dwarf shrub steppes in an irreversible way, but a secondary succession following a disturbance such as plowing and seeding may aid the restoration. We studied degraded Festuca gracillima grasslands (Fg site) and Lepidophyllum cupressiforme shrublands in salty nitric soils (MV site) that had been plowed, seeded, and seasonally grazed thereafter with sheep. The pastures (100- 500 ha) were: recent (1 year in Fg and 7 yrs in Mv), intermediate (11 yrs), and old (16 yrs). Vegetation was assessed using 3 500-point transects in each pasture and 0-20 cm soil samples were obtained and analyzed in a laboratory. A Canonical Correspondence analysis using soil and vegetation properties arranged transects of the Fg site according to age since sowing, but this did not happen in Mv. In Fg introduced Agropyron sp. and Dactylis glomerata dominated initially but grasses and native forbs were recruited subsequently (Poa spiciformis, Deschampsia patula and Carex andina) and finally some psamophyle grasses were incorporated (Pappostipa chrysophylla and Pappostipa ibarii). Cover and diversity were partially recovered in this relatively short time, showing that these semiarid rangelands retain resilience and restoration potential after a disturbance